RANCANG BANGUN APLIKASI DATA TENAGA PENGAJAR PENDIDIKAN ANAK USIA DINI (PAUD) PADA UNIT PELAYANAN TERPADU (UPT) DINAS PENDIDIKAN RANTAU SELATAN BERBASIS WEB - Ainun Ainun; Kusmanto Kusmanto (U-NET Jurnal Teknik Informatika, 2018)
Early Childhood Education (PAUD) is one of the coaching efforts aimed at children from birth up to six years conducted through the provision of educational stimuli to help physical and spiritual growth and development so that children have readiness to enter further education. White box testing is a test that is based on checking the details of the design in order to get the correct program as a whole, while black box testing is a test that is carried out only observing the results through test data and functional checking of the software. With the application of this website, it can facilitate the employees of the Integrated Services Unit (UPT) of the South Rantau Education Office in processing data of early childhood education teachers (paud) accurately and accurately. To facilitate the employees of the Integrated Services Unit (UPT) of the South Rantau Education Office the application was designed by the author using the web, because the web is a system that is widely used both agencies and other companies